Radio emission and mass loss rate limits of four young solar-type stars - Fichtinger, B.; Güdel, M.; Mutel, R.; Hallinan, G.; Gaidos, E.; Skinner, S.; Lynch, Christene; Gayley, K. (EDP Sciences, 2017)
Aims. Observations of free-free continuum radio emission of four young main-sequence solar-type stars (EK Dra, p1UMa, ?1Ori, and ?1Cet) are studied to detect stellar winds or at least to place upper limits on their thermal radio emission, which is dominated by the ionized wind. The stars in our sample are members of The Sun in Time programme and cover ages of ~0.1-0.65 Gyr on the main-sequence. They are similar in magnetic activity to the Sun and thus are excellent proxies for representing the young Sun. Upper limits on mass loss rates for this sample of stars are calculated using their observational radio emission. Our aim is to re-examine the faint young Sun paradox by assuming that the young Sun was more massive in its past, and hence to find a possible solution for this famous problem. Methods. The observations of our sample are performed with the Karl G. Jansky Very Large Array (VLA) with excellent sensitivity, using the C-band receiver from 4-8 GHz and the Ku-band from 12-18 GHz. Atacama Large Millimeter/Submillitmeter Array (ALMA) observations are performed at 100 GHz. The Common Astronomy Software Application (CASA) package is used for the data preparation, reduction, calibration, and imaging. For the estimation of the mass loss limits, spherically symmetric winds and stationary, anisotropic, ionized winds are assumed. We compare our results to 1) mass loss rate estimates of theoretical rotational evolution models; and 2) to results of the indirect technique of determining mass loss rates: Lyman-a absorption. Results. We are able to derive the most stringent direct upper limits on mass loss so far from radio observations. Two objects, EK Dra and ?1Ori, are detected at 6 and 14 GHz down to an excellent noise level. These stars are very active and additional radio emission identified as non-thermal emission was detected, but limits for the mass loss rates of these objects are still derived. The emission of ?1Ori does not come from the main target itself, but from its M-dwarf companion. The stars p1UMa and ?1Cet were not detected in either C-band or in Ku-band. For these objects we give upper limits to their radio free-free emission and calculate upper limits to their mass loss rates. Finally, we reproduce the evolution of the Sun and derive an estimate for the solar mass of the Sun at a younger age.